Reconstruction of Article 280 Section 1 Law Number 7 of 2017 concerning Election - Hamzah, Yusuf (Universitas Negeri Gorontalo, 2021)
This study aims to analyze the regulation of Article 280 paragraph (1) of Law Number 7 of 2017 concerning general elections by the Gorontalo Province Election Control Board. This research belongs to the type of sociological or empirical research with a qualitative research approach. The data analysis technique used in this research is using qualitative data analysis. The results of this study indicate that the form of regulation carried out by Election Control Board is through 2 (two) things, namely prevention which includes socialization to the community, political parties, government, related to early prevention of violations of Money Politics. and coordinate with related parties as well as take action against the alleged practice of Money Politics in the 2019 legislative elections covering the entire area of the Election Control Board of Gorontalo Province. The urgency of the ideal regulation of preventing the practice of Political Money in the Legislative Elections is 1). Revise article 280 paragraph (1) of Law Number 7 of 2017 concerning Elections by changing the redaction of the sentence â€œExecutor, Participant or Campaign Teamâ€ to â€œEveryoneâ€; 2). Implementation of political education to the public involving political parties, Election Control Board, Electoral Commission, Attorney General's Office, and the National Police; 3). As well as increasing the time for handling violations of Money Politics practices by the Election Control Board.